Implementation of Octalysis-Based Gamification Method Cross-Platform For Design of Time Management Application - Christopher, Kurnia; Adline Twince Tobing, Fenina (The Indonesian Journal of Computer Science, 2024)
Time management is an important skill in college. The greater the student's skill in managing his time, the greater the student's academic performance. However, there are students who do not have these skills and almost drop out of college. Therefore, application design and development are carried out.time management using the Octalysis framework gamification method, which is cross-platform-based so it can be accessed anywhere. The application has been completed and has been evaluated by 31 respondents using the Unified Theory of Acceptance and Use of Technology Model (UTAUT), amounting to 83.20%. From the results of this evaluation, it can be concluded that the time management application was well received by students